Analysing the influential factors of sustainable housing affordability in Malaysia - Then, Sin Yee (2021)
Housing affordability has become a pressing concern across the globe. Accordingly, there are real tensions in the policy planning to provide affordable housing, as well as achieve sustainable development. In order to abate this issue, a total of 20 critical factors influencing sustainable affordable housing, housing preferences based on 7 different demographic factors and 10 policy tactics to mitigate affordable housing gap were determined through comprehensive literature review in this research. This study adopted quantitative research method by which the data were acquired from 120 respondents through questionnaire survey within the Klang Valley area. Subsequently, the reliability of the data was tested by using Cronbach’s reliability test. Internal consistency has been achieved and thus the data is valid to proceed for other tests. For mean ranking, the top five most agreed influential factors of sustainable housing affordability were revealed as: (1) Housing price in relation to income; (2) Crime rate; (3) Availability of mortgage and interest rate; (4) Rental price in relation to income; (5) Employment opportunities accessibility. Meanwhile, (1) Crime rate, (2) Housing price in relation to income and (3) Quality performance of housing were perceived as first three fundamental housing preferences amongst respondents. Furthermore, the top 3 strategic measures to reduce affordable housing gap were (1) Mitigate rejection of housing loans from bank, (2) Reduce the construction cost for affordable housing and (3) Provide housing schemes. Furthermore, Kruskal-Wallis test indicated that there are significant differences between respondents groups’ perceptions on the variables. Lastly, factor analysis has uncovered a total of 5 underlying factors, namely values and lifestyles, safety and satisfactions, economic sustainability, environmental and accessibility. By identifying the influential factors of sustainable affordable housing, these could be pivotal interventions to provide insight to real estate developers, government agencies and architects to rely on these influential factors in the affordable housing projects.